Establishing a baseline: A social realist perspective on academic advising at a South African university prior to COVID-19 - de Klerk, D. (South African Journal of Higher Education, 2023)
Academic advising remains an emerging practice and profession within the South African higher education sector. Although there has been an increase in literature about advising in South Africa recently, there remains a dearth of literature about the experiences of academic advisors working in this context. This article aims to make such a contribution, by focusing in particular on the experiences and insights from 15 South African advisors (from one university) about academic advising prior to the COVID-19 pandemic. The data that informs this study was collected through semi-structured interviews. The focus in this article is on advisor responses to three of the interview questions, which proved sufficient because of the richness of the data. The study draws on elements of social realist Margaret Archer’s (1995) morphogenetic framework to explicate why this perspective on advising within a South African higher education context is necessary. Archer’s (1995, 2005) work on structure, culture, and agency is then used as analytic lenses with which to analyse the advisors’ experiences and insights of advising prior to the pandemic. A phenomenographic approach (Marton 1981; Tight 2016) is adopted to explore the varying conceptions (Cibangu and Hepworth 2016) of advising offered by the academic advisors. Nine focal areas emerge from these insights, which are analysed and discussed using Archer’s (1995, 2005) structure, culture, and agency. It becomes apparent that academic advising was complex even before the pandemic. The advisors express an urgency to help others, raise concerns about entrenched inequities and resource constraints, highlight the pitfalls of inadequate help-seeking among students, and emphasise the need for better institutional integration of academic advising at the advisors’ university, among other things. It becomes clear that there are numerous structural and cultural tensions that constrain advisor and student agency, possibly to the detriment of student success. The article leaves the reader with insights into the experiences of academic advisors prior to the pandemic, thus providing a baseline against which to measure advising during and beyond the pandemic, at a time when advising in South African higher education is still being developed and defined.